STRATEGY FOR PREVENTION OF JAMMED CREDIT AND FINANCING DEVELOPMENT TO IMPROVE PROFITABILITY (CASE STUDY PT.BNI SYARIAH KCU MEDAN) - Raja Sakti Putra Harahap; Nur Intan Sari (Proceeding International Seminar of Islamic Studies, 2021)
This research is motivated of daily banking activities. Where, as we know, the general activities of the bank are collecting funds from the public in the form of savings and channeling these funds back to the public in the form of credit and providing other bank services in order to improve the lives of many people. From this background, problems arise regarding the distribution of funds (credit), namely how to prevent bad credit strategies, development of financing, constraints and impacts as well as the advantages and disadvantages of financing at PT.BNI Syariah KCU Medan. This study aims to determine the steps taken by PT. BNI Syariah KCU Medan in solving problematic financing and whether the method used is in accordance with the Sharia Banking Law and the MUI DSN Fatwa. This research is a descriptive qualitative research, which is looking for data directly into the field and literature study. The literature study was carried out by means of observation and in-depth interviews. Based on the results of research and discussion, the conclusion is that the steps taken of PT. BNI Syariah KCU Medan in solving problematic financing, namely by using the non-litigation channel and the litigation channel. The non-litigation channel is carried out by taking over the debtor's collateral (asset-settlement), while the settlement by litigation can be carried out by executing a certificate of mortgage and collateral auction via an execution auction (auction via court order). Troubled financing can be avoided through the implementation of coaching and supervision of financing carried out by all parties PT. BNI Syariah KCU Medan.Keywords: Problem Financing, PT. BNI Syariah KCU Medan